Neoliberal Postmodernity and Hyperimperialism - O. N. Misko; P. I. Sysoev (Евразийская интеграция: экономика, право, политика, 2022)
The article describes transformation of the ideology of liberalism and the associated practices of economic domination at the transition stage from the socio-philosophical Modern paradigm to Postmodern paradigm.Aim. Identify the link between the rhetoric of modern liberalism, Postmodern paradigms and trends in the evolution of the world economic system.Tasks. Consider the historical conditions for the formation of liberal and neo liberal ideology; determine the place of neoliberal discourse in the ideological landscape of our time; correlate it with other relevant discourses that claim to explain economic, social and cultural processes; to analyze the features of modern practices of developed countries economic domination in relations with the others world countries.Methods. The article, using logical analysis, establishes the main features of modern liberal ideology, allowing us to talk about a new stage in the history of the liberalism development. Comparative analysis allows us to find out the points of liberalism convergence at this stage with other ideological directions in present time. However, statistical analysis reveals important economic factors impeding the reduction of the distance between developed and developing countries.Results. The study showed that to date, the liberal discourse has undergone significant changes, which allows us to talk about a completely new stage in the development of liberal ideology. On the one hand, it was significantly influenced by a general paradigm shift that affected the entire spectrum of socio-economic thought in the 20th century, which we define as an intensifying transition from the Modern paradigm to the Postmodern paradigm. On the other hand, the analysis of the historical path of imperialism and its inherent practices of domination also allows us to talk about its sig nificant transformation in the conditions of the post-industrial economy and the information society. Parallel consideration of these aspects (ideological and practical), the continuous correlation of theory with economic realities allows the authors to define such a complex concept as hyper imperialism. This term is proposed to be used to refer to a specific form of imperialism in a post-industrial manner. At the same time, the intrinsic inseparability of various types of expansion — economic, ideological and, more broadly, civilizational — is taken as its key feature.Conclusion. In the context of a large-scale socio-economic and ideological transformation of a global nature, the need for new forms and means of confronting economic hegemony and finding a path to independent economic and social development is increasing.